Operation of slope-assisted Brillouin optical correlation-domain reflectometry: comparison of system output with actual frequency shift distribution - Lee, Heeyoung; Hayashi, Neisei; Mizuno, Yosuke; Nakamura, Kentaro (Optics express, 2016)
Although the proof of concept for slope-assisted (SA-) Brillouin optical correlation-domain reflectometry (BOCDR) has been demonstrated, no reports on its detailed operation have been provided to date. We theoretically and experimentally investigate the relationship between the system output (power-change distribution) of SA-BOCDR and the actual Brillouin frequency shift (BFS) distribution along the sensing fiber and show that these two are not identical. When the strained fiber section is much longer than the nominal spatial resolution, the actual distribution of the BFS (i.e., strain) is well reproduced by the power-change distribution. However, when the length of the strained section is equal to or only a few times the nominal resolution, the correct BFS distribution cannot be directly obtained. Even when the strained section is shorter than the nominal resolution, a shift in the power change can still be observed, which is not the case for standard BOCDR systems. This unique "beyond-nominal-resolution" effect will be of great use in practical applications.